2017
DOI: 10.5662/wjm.v7.i4.139
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of cranial approaches in the anatomy laboratory: A neuronavigation based research method

Abstract: AIMTo describe the development and validation of a novel neuronavigation-based method, which allows the quantification of the anatomical features that define an approach, as well as real-time visualization of the surgical pyramid.METHODSThe method was initially developed with commercially-available hardware for coordinate collection (a digitizer and a frameless navigation system) and software for volume rendering; dedicated neuronavigation software (ApproachViewer, part of GTx-UHN) was then developed. The accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Following deduplication and abstract review, 51 relevant articles were identified. Thereafter remained fourteen primary papers [ 8 , 17 , 20 , 26 , 33 , 34 , 37 , 39 , 46 , 51 , 55 , 58 – 60 ], and 37 secondary papers [ 1 5 , 9 12 , 14 16 , 23 , 27 , 29 32 , 35 , 36 , 38 , 40 , 43 45 , 47 50 , 52 54 , 57 , 62 , 64 – 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Following deduplication and abstract review, 51 relevant articles were identified. Thereafter remained fourteen primary papers [ 8 , 17 , 20 , 26 , 33 , 34 , 37 , 39 , 46 , 51 , 55 , 58 – 60 ], and 37 secondary papers [ 1 5 , 9 12 , 14 16 , 23 , 27 , 29 32 , 35 , 36 , 38 , 40 , 43 45 , 47 50 , 52 54 , 57 , 62 , 64 – 66 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Our group has been working with an in-house navigation software package (GTx-Eyes) [ 81 ] mostly in pre-clinical settings [ 10 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], and in proof-of-principle clinical studies [ 66 , 86 , 93 , 94 , 95 , 96 ] with proven benefits.…”
Section: The Gtx Lab Experiencementioning
confidence: 99%
“…The GTx-Eyes software displays a three-dimensional image of a cone-beam computed tomography (CBCT) obtained from cadaver specimens or artificial skull models [ 88 , 97 ]. This technology allows the surgeon to locate a registered instrument or pointer tool superimposed on two-dimensional tri-planar views (e.g., axial, sagittal, coronal).…”
Section: The Gtx Lab Experiencementioning
confidence: 99%
See 2 more Smart Citations